By any sacramental means necessary: Baptism as engaged defiance of ecocide and empire. Issue 3 (4th July 2022) - Vander Tuig, Adam
Abstract: By the end of his life, Malcolm X had become synonymous with the phrase, "by any means necessary." With this philosophy he expanded the black freedom struggle of his day, adding new urgency, militancy, and sobriety to the movement. The Evangelical Lutheran Church in America (ELCA) has named God's gifts of Word and Sacrament the "means of grace." Held up to the revolutionary philosophy of Malcolm X, the degree to which our baptismal means have become domesticated and depoliticized becomes troublingly clear. This paper addresses these problems and offers a way forward. The special relationship that God, Jesus, and even Martin Luther had with water—to say nothing of our ongoing climate catastrophe—compels us to begin by rewatering and repoliticizing the entire baptismal process, introducing new urgency, militancy, and sobriety to our once revolutionary sacrament.